OzoNews Volume XXII - 15 February 2022 - United Nations Environment Programme (2022)
In this issue: 1. Kigali Amendment latest ratifications 2. Cooling Matters: World Refrigeration Day Announces 2022 Theme 3. The influence of iodine on the Antarctic stratospheric ozone hole 4. Call for nominations now open for Scientific Prizes at IIR Congress 2023 5. Women working for the Montreal Protocol and environmental protection 6. Marine Environment-What are Ozone Depleting Substances on Ships? 7. Liberia: Refrigeration, Air-conditioning Technicians Trained 8. West Africa marks journey to household energy efficiency under ECOWAS 9. Thailand: Go hand in hand with 3 agencies to reduce and stop ozone layer depleting substances 10. Syria Keeps Pace with Montreal Protocol Implementation 11. Oman: Committee formed to tackle Climate Change and Ozone Layer Protection 12. Nicaragua Ministerio del Ambiente y Recursos Naturales (Marena) celebra encuentro ambiental con importadores de sustancias refrigerantes 13. HFC Policies & Refrigerant Regulations by State 14. Alternative Refrigerants for Commercial Refrigeration 15. EU’s ENOUGH Project to Address Cooling and Heating Emissions in Food Industry 16. New environmental labelling system unveiled 17. Switch to dry powder inhaler more than halves carbon footprint of asthma treatment